Water Environmental Carrying Capacity for Activities of Intensive Shrimp Farm in Banyuputih Sub-District, Situbondo Regency - Abdul Muqsith; Nurdin Harahab; Mohammad Mahmudi (Indonesian Journal of Environment and Sustainable Development, 2014)
This research was aimed to determine the width area of an intensive shrimp farm which can be supported by water environment of Banyuputih Sub-District, Situbondo Regency according to the water assimilation capacity towards the farm’s organic waste. We used survey method and secondary data collection from other researches or result report of relevant institution. This study was using two approaches of environmental carrying capacities, i.e. (1) quantitative method on available water volume in coast (coastal water) and (2) quantitative method on available Dissolved Oxygen (DO) in waste receiving water body of coastal water. The result showed that the utilization of coastal area for intensive shrimp farm activities in this study area is not exceeding its carrying capacity of water yet. Based on the analysis, the water environmental carrying capacity for the farm’s organic waste is 375.637 kg TSS. Organic waste (TSS) disposed from an intensive shrimp cultivation at the study area is 6.506 kg TSS.ha-1.MT-1. The width of intensive area which can be supported by Banyuputih Situbondo water environment is 58 ha. The width of available intensive pond area at study site is 113 ha, but only 39 ha is active/productive, the remaining 74 ha is inactive/unproductive area. If unproductive area will be re-operated/reactivated again, then we would recommend only 19 ha according to the water environment carrying capacity for the farm’s organic waste (58 ha). Estimation result of water environment carrying capacity for this organic waste of shrimp farm can be used as reference to determine the development or management threshold of sustainable pond area at this study site.   Keywords: environment carrying capacity, organic waste, shrimp farm